Seksualność w socjotechnice dyscyplinowania - Pawełczyk, Piotr (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The paper ponders the subject of utilizing human sexuality in the process of social disci- pline. The author perceives this process as a modern form to subjugate an individual primarily on the basis of symbolic coercion. Making reference to the classical works of Michel Foucault the author emphasizes the factors that allow sexuality to be used for social programming. Foucault was critical of the idea that we experience the repression of a natural sexual drive, at least in its traditional meaning. In his opinion, multiplied knowledge of sex should be noted in Western societies, which leads to the hyper-development of sexual discourse, theory and the science of sexuality. He questioned the stereotypical understanding of sexual repressiveness, which determines a way of thinking in terms of a simple retaliation taken for inappropriate sexual behavior. He suggested that less observable programming control be introduced in- stead, based on disciplining. The limits of discourse are established by the admissible sexual relations. Whatever goes beyond this discourse, whatever is not contained within it, becomes abnormal and, potentially, repressed. The objectives of programming control and the limits of discipline are decided not only by the church and state, but also by business and media con- cerns, which fill the discourse with certain subjects thus deciding what dimensions of sexual- ity are permissible. Confessions that used to be confined to confessionals and psychoanalysts’ surgeries have become media commodities used not only marginally by pornography, but for- matted to excite, fill voyeuristic needs and experience vicarious sensations. Discourse is be- coming an area of apparent freedom, whereas in fact it is a means to discipline society. This seeming expansion of discourse limits to a lesser degree concerns the realm of problems and to a greater degree – accessibility. What used to be an object of communicative interest re- served for the elite has been included in mass discourse because this is the requirement of modern democracy and a liberal economy.
Sexuality in the Process of Social Discipline
Keywords: socjotechnika; seksualność